Differences between physical therapist ratings, self-ratings, and posturographic measures when assessing static balance exercise intensity - Jamie Ferris; Jonathan Zwier; Wendy J. Carender; Kathleen H. Sienko (Frontiers Media S.A., 2023)
IntroductionIn order for balance therapy to be successful, the training must occur at the appropriate dosage. However, physical therapist (PT) visual evaluation, the current standard of care for intensity assessment, is not always effective during telerehabilitation. Alternative balance exercise intensity assessment methods have not previously been compared to expert PT evaluations. The aim of this study was therefore to assess the relationship between PT participant ratings of standing balance exercise intensity and balance participant self-ratings or quantitative posturographic measures.MethodsTen balance participants with age or vestibular disorder-related balance concerns completed a total of 450 standing balance exercises (three trials each of 150 exercises) while wearing an inertial measurement unit on their lower back. They provided per-trial and per-exercise self-ratings of balance intensity on a scale from 1 (steady) to 5 (loss of balance). Eight PT participants reviewed video recordings and provided a total of 1,935 per-trial and 645 per-exercise balance intensity expert ratings.ResultsPT ratings were of good inter-rater reliability and significantly correlated with exercise difficulty, supporting the use of this intensity scale. Per-trial and per-exercise PT ratings were significantly correlated with both self-ratings (r = 0.77-0.79) and kinematic data (r = 0.35-0.74). However, the self-ratings were significantly lower than the PT ratings (difference of 0.314-0.385). Resulting predictions from self-ratings or kinematic data agreed with PT ratings approximately 43.0-52.4% of the time, and agreement was highest for ratings of a 5.DiscussionThese preliminary findings suggested that self-ratings best indicated two intensity levels (i.e., higher/lower) and sway kinematics were most reliable at intensity extremes.